Estimasi Volume Penumpang Pesawat Udara di Bandar Udara Internasional Adisutjipto Menggunakan Model Gravity - Gunawan, Gunawan; Mauidzoh, Uyuunul; Adiputra, Bangga Dirgantara; Dinaryanto, Okto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Demand forecasting is used by airlines to predict the travel behavior of potential passengers. Accurate forecasting is critical to the overall success of an airline. An important element in forecasting is passenger volume estimation. The goal is to predict the number of passengers expected between two cities for a given time interval. Based on this forecast, airlines can make decisions about new routes or additional flights on existing routes. Starting January 2020, all flights to Yogyakarta have landed at Yogyakarta International Airport (YIA) except for flights using propeller aircraft such as ATR which can still use Adisutjipto International Airport (JOG). Adisutjipto International Airport currently only serves 3 routes, namely Yogyakarta (JOG) - Jakarta (HLP) RT., Yogyakarta (JOG) - Bandung (BDO) RT., and Yogyakarta (JOG) - Surabaya (SUB) RT.. The opening of Adisutjipto International Airport to propeller aircraft makes it possible to increase flight frequencies or new routes. For that, it is necessary to estimate the volume of aircraft passengers at Adisutjipto International Airport using the gravity model. The most accurate model is Model 5, where the attraction force is separated into the number of residents of the origin and destination zones and the GRDP of the origin and destination zones, as well as the distance impedance factor and ticket rates are also separated.